A man for all seasons - Bolt, robert; Colicos, John, 1928-2000.; Graham, William H. (Director); Bolt, Robert; Olney Theatre (Organization : Olney, Md.); Richard L. Coe Theater Programs Collection (Library of Congress) (London : Heinemann, 1960)
Olney Theatre, John Colicos in "A Man for All Seasons," by Robert Bolt, with David Sabin, Richard Bauer, Mark Hammer, Richard Curnock, Robert Milli, Al Corbin, Anne Chodoff, Halo Wines, directed by W.H. Graham, settings and lighting by James D. Waring, costumes by Joseph Lewis.
Olney Theatre, Jult 13-31, 1966.
Title devised by Library staff.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Maryland -- Olney; Theater programs